Pengaruh Pemberian Musik Terhadap Tingkat Stres Kerja Karyawan Di Bagian Batik Tulis Griya Batik Brotoseno Masaran Sragen - , Winarsih; , dr. Hardjanto, M.S., Sp.OK; , dr. Suwadji, M.Kes (2015)
Work stress is a result of the working process. One of the factors that can decrease the level of work stress is comfortable working environment, for example by providing music during employee work. This study aimed to determine the effect of providing music toward levels of work stress on batik tulis section workers at Griya Batik Brotoseno Masaran Sragen. This research method is Quasi Eksperiment with One Group Pre Test Post test Design. The population of this study were 85 female workers at the batik tulis section. The sampling technique using purposive sampling. Statistical test with a significant level (α = 0.05) using Paired sample t-test. Statistical analysis showed that there is an effect of providing music on employee's stress levels (p-value = 0.000). Employee's stress levels can be decreased from the medium stress become a mild stress. Providing music while working adapted to the type of music preferred by the workforce.